Serial Mediation Effects on Relationships among Mobbing, Organizational Cynicism, Job Satisfaction and Turnover Intention: Research on Disabled Individuals in Organizations - Tezcan Zeynep Özkan Tilki; Semra Güney; Selin Metin Camgöz (Psikoloji Çalışmaları)
More than one billion people in the world are living with disabilities, however, the challenges that these individuals face are not being discussed in the social and business realm. Consequently, there are very studies conducted for disabled employees in organizations. Taking this into consideration, the purpose of this study is to observe the effects of serial mediation among the relationships of mobbing, organizational cynicism, job satisfaction, and turnover intention. The sample of the study was comprised of 184 individuals who have a variety of disabilities such as physical, hearing, speech, and learning difficulties, as well as chronic diseases, working in private and state organizations within different sectors. The data was gathered by survey through convenience and snow ball sampling methods. The 40% disability rate used in the public sector was the determining factor of the inclusion criteria. Individuals that had a disability report at this rate or above were accepted as disabled and considered to be part of the study. The first part of the study comprised of determining the factorial structure of items in the scales utilizing the Confirmatory Factor Analysis (CFA). After examining the fit indices, it was concluded that the data set fit well within the measurement model. Serial multiple mediation analysis was used to test the proposed hypotheses of the study. The findings revealed that mobbing has an indirect effect on turnover intentions via the serial mediating effects of organizational cynicism and job satisfaction. In other words, as mobbing toward disabled workers increases, the level of organizational cynicism also increases. As a result, the job satisfaction decreases and thus results in higher levels of turnover intention in disabled individuals. The importance of looking at work-related problems with a social model approach that suggests that the problems are related to the perspective of the society rather than looking as a deficiency arising from individuals with disabilities has been emphasized once again with this study. The study also sheds light on the importance of creating necessary practices that determine the effects that negative behaviors and attitudes have toward individuals with disabilities within the work environment.